Towards Critical Literacy Approaches in Access to Information Resources by Students in Selected University Libraries in Kenya. - Mutegi, James Njue (UoEm, 2025)
The future of university libraries relies on Critical Information Literacy (CIL) to empower students, challenge traditional systems, and ensure fair access to knowledge. CIL interrogates the effectiveness of Information Literacy (IL), disrupts inequitable systems, and creates student-driven training. Further, it supports inclusive and ethical publishing models while rejecting the notion of libraries as neutral spaces. CIL and Metaliteracy are interdependent. Metaliteracy is a form of user education that promotes critical thinking and collaboration in a digital age, providing a comprehensive framework to effectively participate in social media and online communities. This study aimed to investigate CIL approaches and how students can improve access to information in selected university libraries and provide a framework for the same. The objectives of this study were to: examine the types of CIL information resources that the selected university libraries offer; analyze the methods used by librarians in implementing CIL; explore the factors affecting the implementation of CIL in selected university libraries, and propose a framework to enhance CIL in selected university libraries in Kenya. The Social Cognitive Theory (SCT) and Critical Research Paradigm (CRP) provided a theoretical framework for this study. The research design adopted for this study was a convergent parallel mixed method containing both qualitative and quantitative approaches. The study targeted a population of 473 respondents comprising 431 undergraduate and postgraduate students, 28 ICT/Reference Librarians, and 14 University Librarians. Based on the inclusion and exclusion criteria, the final population consisted of 337 undergraduate students, 94 postgraduate students, 28 ICT/Reference Librarians, and 14 University Librarians. A census approach was adopted to involve all 473 eligible respondents in the study. Quantitative and qualitative data were collected using questionnaires and key informant interviews. Quantitative data was analyzed using SPSS, and qualitative data was collected using Atlas. ti. The study findings established that the selected university libraries offered a range of CIL resources for students, with library OPAC and LCC leading and shelf signage being the least offered CIL resources. Findings also revealed that the selected university libraries offered various CIL methods, with library orientation leading and feminist pedagogy being the least offered. Among the challenges were a lack of trained librarians to teach CIL, power dynamics, inadequate ICT infrastructure, and a lack of interest in learning CIL. The study concluded that several challenges confronted CIL resources and delivery methods, and that students lacked self-efficacy in the use of CIL resources and methods of teaching. The study recommended developing national guidelines on CIL approaches and drawing principles for implementing CIL. The other recommendations of the study were awareness creation on CIL resources, enhancement of CIL resources, enhancing students’ metaliteracy skills, faculty and librarian collaboration, developing CIL Curriculum, establishing a feedback mechanism, and providing librarian support. Keywords: Access, Critical Information Literacy, Metaliteracy, Critical Librarianship, Librarian power, University library, University Librarian
Thesis
Keywords: Access; Critical Information Literacy; Metaliteracy; Critical Librarianship; Librarian power; University library; University Librarian